ANALISIS EFEKTIVITAS KINERJA DAN KONTRIBUSI RETRIBUSI PEMAKAIAN KEKAYAAN DAERAH TERHADAP PENDAPATAN ASLI DAERAH - Manuputty, William J.; Saerang, David P. E.; Alexander, Stanly W. (JURNAL RISET AKUNTANSI GOING CONCERN, 2019)
Retribution is one of the income obtained by various services given or certain permits by the government and one of the agencies that process it is BPPRD, in the North Sulawesi Province BPPRD there is acceptance of many types of retribution one of which is regional wealth usage retribution. The purpose of the authors in this study is to find out the effectiveness of performance and the contribution of retribution on the use of regional wealth in PAD which is a regional development resource analyzed by qualitative methods. The results obtained through this research are able to determine the effectiveness of regional wealth retribution for the past five years is very good in its realization with an average percentage 91,9% with its contribution to local revenue at 0,17%.Keywords : retribution, local revenue, performance efectivity